Isolation of Expressed Sequence Tags (Ests) from an Oil Palm (Elaeis Guineensis Jacq.) Male and Female Floral cDNA Library - Choi, Mei Chooi (2003)
The bottleneck of the current knowledge in understanding the oil palm flower development in term of abnormalities and sex ratio is the low number of known flower genes available. The shortage of these genes is a serious constraint in studying the mechanisms regulating gene expression in flowers. Therefore, it is vital to obtain as much information as possible on the complexity and type of genes expressed in the oil palm floral organ. To dissect the molecular mechanisms underlying these development processes, a vast amount of genetic resources are required as markers that would enable a complete picture of the complex floral development processes in oil palm to be determined. In this study, expressed sequence tags (ESTs) were used as a genetic resource to facilitate the identification of new gene markers on a large-scale basis and also to provide information on gene expression patterns. To date, about 1,600 EST clones were isolated and sequenced using cold plaque screening method. Among the 1,600 ESTs generated from eDNA libraries of oil palm flowers, 266 independent clones with insert size of more than 500bp were subjected to reverse Northern analysis and this has resulted in classification into 5 major subpopulations (opff and opmf) based on the level and specificity of expression. Subpopulation A consisted of clones that were highly expressed in all the tissues (41%) whereas sUbpopulation B contained clones that were female predominant and expressed at medium levels (23.3%). Subpopulation C and D consisted of clones that were expressed at low levels predominantly in the flower (17.7%) and young leaf (6%), respectively. The last group, subpopulation E contained all the clones that showed no hybridization signals to all the tissues (12%). Further characterization of selected opff and opmJ clones by sequence analysis has revealed 3 maj or classes of ESTs. Class A consisted of sequences with similarity to known proteins in the database (56%) while class B showed sequences similar to proteins with unknown function (30%) and class C showed no sequence similarity to proteins in the database (14%). Two clones were selected among the cDNA clones identified that have sequence homology to known sequences in database to be further characterized. They were putatively known as Squamosa Promoter Binding Protein (OPSBP) and GAstimulated transcript 1 (OPGAST), respectively. OPSBP was found to be constitutively expressed throughout flower developement and was localized to bracts, rachis and carpels. On the other hand, OPGAST was found ubiquitously expressed in all flower tissues but the transcript levels were higher in the shoot apex. This study suggested that OPSBP appears to be up-regulated during early flower development.Further characterization of these "clones by Southern genomic hybridization showed that OPSBP and OPGAST exist as a single copy gene and mUlti-copy genes, respectively, in the oil palm genome. In summary, the results indicate that the EST approach was efficient in identifying and isolating oil palm floral genes that range from those that are expressed at certain developmental stages to those that have undetectable expression throughout flower development. This achievement also demonstrated that genes isolated by cold plaque screening are not restricted to genes that are tissue specific or developmental stage specific but the technique also enables the isolation of genes that are generally expressed at low levels.